Sosialisasi Penanaman Sopan Santun sebagai Upaya Membangun Karakter Bangsa di MTs Sultan Hasanuddin - Thahir, Muthahharah (Ma'soem University, 2024)
This socialization activity is motivated by the attitude of students who do not respect the role and authority of teachers such as lack of respect, using harsh or inappropriate words in communication, and even non-compliance with discipline. The purpose of this community service program is to provide an understanding of the importance of cultivating good manners at MTs Sultan Hasanuddin. The method in this community service activity is to use PAR (Participatory Action Research) which includes planning, implementation, results and evaluation stages. The results of the activity have been carried out well, the teachers get knowledge about how to instill good manners to students because this is an effort to build national character.